DIVERSITY OF HORNWORT IN MOUNT SLAMET (CENTRAL JAVA) - Arin Ulfiana Mubarokah Siagian; Nunik Sri Ariyanti; Nina Ratna Djuita (PTTI, 2021)
Recent more intensive explorations and collections of hornworts in Mt. Slamet indicated that six species can be recognized, namely Anthoceros punctatus, Folioceros fuciformis, Phaeoceros carolinianus, P. exiguus, Dendroceros difficilis, and Megaceros flagellaris. Since originally only one species D. difficilis was recorded from this area, this means that five species represent new records for the area, whereas P. exiguus is not only a new record for Java, but it is also a new record for Malesia.